INFLUENCE OF THE SCHOOL ADMINISTRATIVE ENVIRONMENT ON THE ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN EDO SOUTH SENATORIAL DISTRICT, EDO STATE - EGHOMWANRE , OSASERE DEBORAH; OGBEIDE, AGBONS KENNEDY (Sokoto Educational Review, 2025)
This study investigated the influence of the school administrative environment on students’ academic performance in secondary schools across Edo South Senatorial District, Edo State, Nigeria. The research explored whether administrative factors such as leadership, infrastructure, school location, school size, and the principal’s gender affect academic outcomes. A descriptive survey research design of a correlational type was employed. The target population consisted of 2,502 teachers and principals from 137 public secondary schools. From this, a sample of 217 respondents was drawn using random sampling. Data were collected through a validated questionnaire titled "Nature of School Administrative Environment Questionnaire (SAEQ)" and a proforma that documented students’ NECO results in English, Mathematics, and Civic Education. The reliability of the questionnaire was confirmed using the split-half method, showing a high consistency score of 0.98. Data analysis was performed using descriptive statistics and mean to answer research questions, and Pearson correlation was used to test hypotheses 1-3. Results indicated that while the overall administrative environment in schools was rated as good, weaknesses were found in school safety and emergency preparedness. The study also revealed that the school administrative environment had a greater influence in large schools compared to small ones and was more positively correlated in schools led by male principals. However, school location (urban vs. rural) showed minimal difference in performance outcomes. The study concluded that strengthening administrative practices in specific areas can lead to improved academic outcomes. It recommends targeted policy and structural reforms aimed at improving safety, equity in leadership effectiveness, and optimal administrative practices across school sizes and locations